Upaya Meningkatkan Hasil Belajar Bahasa Indonesia dengan Model Modeling The Way Berbantuan Media Audio Visual pada SDN V Telangkah Tahun Pelajaran 2016/2017: Efforts to Improve the Result of Learning Indonesian Language with Modeling Model The Way Assisted by Audio Visual Media in SDN V Telangkah 2016/2017 Academic Year - Prestini Prestini; Arif Supriyadi (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to: (1) Describe the activities of students in learning Indonesian with Modeling the Way Model with Audio Visual Media. (2) To improve the learning outcomes of Indonesian Language with the Modeling Model of the Way with Audio Visual Media. The subjects in this study were all Vb grade students of SDN 5 Telangkah with 35 students consisting of 18 men and 17 women. The method used in this study is class action (PTK) which is systematic research in learning activities which is an action in the class simultaneously through self-reflection to improve learning outcomes of students using qualitative and quantitative data analysis. The results of the study showed that: (1) Activities of Vb grade students of SDN 5 Telangkah using the Modeling the Way Model assisted by audiovisual media in learning Indonesian improved. This can be seen from the increase in activity, enthusiasm, and enthusiasm of students in participating in the learning process with an average value of 3.37 in the excellent category. (2) There is an increase in Indonesian language learning outcomes by using the Modeling the Way Model assisted by audio-visual media in Vb grade students of SDN 5 Telangkah. The increase can be seen from the initial test of an average of 61 with classical completeness 37.14% and experiencing a growth in the first cycle with the acquisition of tilapia on average 87 students with 91.42% artistic completeness in Indonesian language subjects especially in drama material discipline.